The establishment of season-specific eutrophication assessment standards for a water-supply reservoir located in Northeast China based on chlorophyll-a levels. (February 2018) - Guo, Jingbo; Zhang, Chongjun; Zheng, Guochen; Xue, Jie; Zhang, Lanhe
Graphical abstract: Highlights: Build-up of season-specific eutrophication assessment standards was essential. Water quality parameters underwent different degrees of seasonal variations. Water quality parameters showed diverse correlations with the Chl-a levels. Phosphorus was the predominant limiting nutrient of eutrophication. The reservoir was generally in a light-eutrophic state. Abstract: Eutrophication has become the primary problem facing most surface water bodies worldwide, especially when the water body serves as a water supply source. Substantial efforts have been made to prevent and control eutrophication from decades ago. Among them, the establishment of eutrophication assessment standards was rather essential. However, until now, there is no authoritative standard established for the assessment of eutrophication level in developing countries such as in China. For water bodies located in the Northeast China, the level of chlorophyll-a (Chl-a), which is proportional to phytoplankton biomass, tends to be subjected to evident seasonal variations as the phytoplankton biomass and species composition are greatly impacted by the seasonally alternated climate, hydrology and pollutants source, which in turn complicated the eutrophication problem. The establishment of season-specific eutrophication assessment standards was thus extremely significant for water bodies located in regions with large air temperature variations. In this study, water quality parameters were detected over five consecutive years (2011–2015) to assess the seasonal trophic state of a water-supply reservoir located in Northeast China. Bivariate and multiple regression were performed between Chl-a and other water quality parameters in different seasons. The trophic state of each season was evaluated by the comprehensive trophic level index and the season-specific eutrophication assessment standards were established. The results showed that phosphorus was the predominant limiting nutrient of eutrophication and the Chl-a levels were seasonally different. The reservoir was generally in a light-eutrophic state. Mesotrophic assessment standards were established for spring, summer and autumn and light-eutrophic assessment standards for autumn based on the water quality data collected. As the predominant nutrient, the concentrations of total phosphorus for the mesotrophic state for spring, summer and autumn were 0.044, 0.028 and 0.038 mg/L, respectively. Moreover, as shown by the mesotrophic and light-eutrophic standards of the autumn, the discrepancy of different parameters between the standards of different trophic level was were not necessarily varied in the same trend. In conclusion, the establishment of season-specific eutrophication standards for water bodies located in regions with large air temperature variations was significant for scientific trophic state evaluation and effective eutrophication control.